Preliminary study on isolation and identification of pasteurella multocida isolated from healthy local breed rabbits - Sia, Kathy Shin Shin. (Universiti Malaysia Sarawak (UNIMAS), 2006)
A total of 55 isolates were tentatively identified as P. mllltocida. The isolates were isolated ITom two local falms -Yu Zhou Fann in Kota Samarahan and Tan Domestic Breeder in Kuching area. Out the 55 isolates, 16 of them were tentatively identified as bacterium P. 111111tocida based on 5 isolates positive for oxidase production and the remanding II were negative in oxidase production. The results for conventional biochemical tests were compared with API 20E and API 20NE kits' results. However, the kits were unsatisfactory in identifying this bacterium. PFGE method were also used for genotyping the isolates. Nonetheless, the method fail to show any relatedness between the isolates due to the over excision of restriction enzyme Apal to the bacteria genome. Therefore, a few samples were selected for 16S rRNA sequencing analysis in order to identify the bacterium. The sequencing results identified that the isolates as non P. multocida. Based on the results obtained, the isolates initially identify as P. multocida were proven to be a difficult process. This indicates the difficultly in isolating this organism from healthy rabbits or this bacterium is actually uncommon in the local breed rabbits.